2022
DOI: 10.1101/2022.01.11.22269049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review and meta-analysis of COVID-19 vaccines safety, tolerability, and efficacy among HIV-infected patients

Abstract: Objective To conduct a comprehensive systematic review and meta-analysis of all recommended SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) vaccines in people living with HIV (PLWH), as well as an overview of the safety, tolerability, and efficacy of the vaccines in PLWH. Methods We searched six databases, Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Medline, Medrxiv, Global research on COVID-19 database, and Google Scholar for studies investigating the effects of SARS-CoV-2 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Concerningly, we found an increasing and high proportion of patients with CD4 <200 cells/µL and VL ≥1000 copies/ml, possibly reflecting gaps in HIV care earlier in the pandemic. Second, we need to determine and implement the most effective SARS-CoV-2 vaccination strategies for PWH [10]. Third, comorbidity diagnosis and management in PWH should be optimized, with a particular focus on diagnosis and treatment of tuberculosis which has been severely impacted by COVID-19 [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerningly, we found an increasing and high proportion of patients with CD4 <200 cells/µL and VL ≥1000 copies/ml, possibly reflecting gaps in HIV care earlier in the pandemic. Second, we need to determine and implement the most effective SARS-CoV-2 vaccination strategies for PWH [10]. Third, comorbidity diagnosis and management in PWH should be optimized, with a particular focus on diagnosis and treatment of tuberculosis which has been severely impacted by COVID-19 [25].…”
Section: Discussionmentioning
confidence: 99%
“…The recent WHO Global Clinical Platform of COVID-19 study showed that being on ART and/or virally suppressed was protective against poor COVID-19 outcomes in hospitalized patients, but there is limited data on all COVID-19 patients including those not admitted, and the effect of immunosuppression before the COVID-19 episode [7, 8]. Furthermore, the effectiveness of vaccination in preventing severe COVID-19 in PWH in this context remains unclear [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…These comorbidities are caused by ART-related in ammation and ongoing immune dysregulation, which may in uence COVID-19 disease severity, the durability of protective antiviral responses, and vaccine responsiveness [19][20][21][22]. According to a recent non-peer reviewed systematic review, COVID-19 vaccines had lower immunogenicity and antigenicity among PLWH, than among HIV negative people [23]. Furthermore, PLWH require more attention during the COVID-19 pandemic because the emergence of Omicron in Southern Africa has raised the question of whether this heavily mutated variant is the result of the HIV pandemic, a common cause of immunode ciency in the region [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the unquestionable usefulness of SARS-CoV-2 vaccination, fragile categories of patients may show a sub-optimal response to vaccines. Older patients and those with primary or secondary immunodeficiencies showed indeed an impaired antibody-mediated response after SARS-CoV-2 vaccination, remaining at high risk for severe COVID-19 (13)(14)(15)(16). The optimal clinical management of SARS-CoV-2 infection in these patients is represented by early diagnosis and treatment with medication able to minimize the risk of progression towards severe disease.…”
Section: Introductionmentioning
confidence: 99%